2016
DOI: 10.1038/srep37893
|View full text |Cite
|
Sign up to set email alerts
|

From Quasi-Planar B56 to Penta-Ring Tubular Ca©B56: Prediction of Metal-Stabilized Ca©B56 as the Embryo of Metal-Doped Boron α-Nanotubes

Abstract: Motifs of planar metalloborophenes, cage-like metalloborospherenes, and metal-centered double-ring tubular boron species have been reported. Based on extensive first-principles theory calculations, we present herein the possibility of doping the quasi-planar C2v B56 (A-1) with an alkaline-earth metal to produce the penta-ring tubular Ca©B56 (B-1) which is the most stable isomer of the system obtained and can be viewed as the embryo of metal-doped (4,0) boron α-nanotube Ca©BNT(4,0) (C-1). Ca©BNT(4,0) (C-1) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Also, the system contains 29 × |4c-2e| bonds with 7 located in the inner region of the cluster and other 22 bonds in the outer region of the quasi-planar system. The remaining 19 bonds have a higher number of centers than 5; thus, these electrons are the π electrons that are part of the delocalized orbitals of the model described in the present study and previously suggested by Li et al 53…”
Section: Methods and Resultssupporting
confidence: 70%
“…Also, the system contains 29 × |4c-2e| bonds with 7 located in the inner region of the cluster and other 22 bonds in the outer region of the quasi-planar system. The remaining 19 bonds have a higher number of centers than 5; thus, these electrons are the π electrons that are part of the delocalized orbitals of the model described in the present study and previously suggested by Li et al 53…”
Section: Methods and Resultssupporting
confidence: 70%
“…In fact, the B 40 cluster is known as a fullerene 8 whereas the B 56 cluster is characterized to have a quasi-planar shape. 9 Evolution of the geometric structures of the pure boron clusters is not fully understood yet. With the aim of designing small stable tubes that can be served as units for building up boron tubes, we have found that incorporation of transition metal atoms into the boron hosts can be regarded as an efficient approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, these pure DR units cannot be used to make longer tubes. In fact, the B 40 cluster is known as a fullerene whereas the B 56 cluster is characterized to have a quasi-planar shape . Evolution of the geometric structures of the pure boron clusters is not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%